Design, synthesis and photoelectrical properties of diphenylamine-containing triphenylamine-based D-D-π-A-type fluorescence dyes. Issue 27 (4th July 2019) - Yuan, Rui; Zhang, Longyan; Chen, Lichuan; Zhang, Haoli; Dou, Pengfei; Ren, Xuanxuan; Chen, Wen; Zhou, Hang; Wan, Yu; Wu, Hui
Graphical abstract: Highlights: Novel triarylamine-based D-D-π-A organic fluorescence dyes were designed. Theoretical calculations were done to evaluate the applicability of the design. The most promising dyes (diphenylamine-containing triarylamine-based dyes) were synthesized. Theoretical calculations, electrochemical properties and optical properties were studied. Some of the dyes performed very well as luminescent material as expected. Abstract: Available online A series of diphenylamine (DPA)-containing triarylamine-based D-D-π-A organic fluorescence dyes were designed under the guidance of theoretical calculations and then synthesized (cyanoacrylic acid, methylene malononitrile or isophorone served as the electron acceptor while ethylene served as the π-bridge). The results of theoretical calculations, electrochemical properties and optical properties tests indicated that the new dyes possessed high thermal stability, desirable HOMO levels and intramolecular charge transfer property. Some of them possessed high fluorescence quantum yields and performed very well as luminescent material as expected. .